DNA Nanogel for Cancer Therapy. Issue 4 (8th February 2023) - Zhang, Xiaonong; Yan, Wei; Song, Zhengwei; Asif, Sabahat; Hussain, Irshad; Xiao, Chunsheng; Chen, Xuesi
Abstract: DNA nanogel exhibits properties of both the DNA and hydrogel, for example, remarkable biocompatibility, programmability, high drug loading capacity, and rapid stimuli‐responsive nature to microenvironment, which make it a potential ideal carrier for drug and gene delivery. In this review, DNA nanogels are categorized into two types, that is, rolling circle amplification‐based nanogel and hybridization‐based nanogel. Construction methods, design ideas for different functions, and applications in chemotherapy, gene therapy, and immunotherapy of nanogels are discussed. It is believed that this review will help readers to have a deeper understanding of the basic design strategies of DNA nanogels for specific targeting, loading of various anticancer agents, and stimuli‐responsive degradation of nanogels for the controlled release of drugs, which will ultimately help to design more effective delivery system for better therapeutic effects. It is very likely that DNA nanogel, as an intelligent drug carrier, will play a greater role in cancer treatment in future. Abstract : This review focuses on DNA nanogels based on pure DNA materials and these DNA nanogels are categorized into two types depending on their construction methods. Recent advances on the fabrication of DNA nanogels with high target ability and stimuli‐responsive capability are summarized. Furthermore, emerging applications of DNA nanogels for improved cancer therapy are also discussed.